Does IVF Treatment (Autologous and Donor Oocyte) Improve Pregnancy Outcomes in Women 40 Years and Older? [24K]. (May 2017) - Savasan, Zeynep Alpay; Heasley, Emily; Abdulahad, Aseel; Zeb, Amna
Abstract : INTRODUCTION: Determine perinatal outcomes in women older than 40 years with IVF treatment (autologous and donor oocyte) compared with spontaneous pregnancy (SP). METHODS: Retrospective case control study of singleton pregnancies with maternal age 40 years and older between 2012-2014. Adverse perinatal outcomes included preterm delivery (PTD), hypertensive disorders of pregnancy (HDP), cesarean section (CS), gestational diabetes (GDM), intrauterine growth restriction (IUGR) and fetal loss (IUFD). Composite neonatal outcomes (CNO) included respiratory distress, intraventricular hemorrhage, necrotizing colitis, jaundice, NICU admission and neonatal death. RESULTS: Among 249 patients, 102 were IVF conceptions. Median maternal age (years) was 41 (40-50) for SP and 43 (40-52) for IVF (p>0.05). Logistic regression showed OR for PTD 2.3 (95% CI:1.1-4.7; p=0.024), HDP 2.5 (95% CI:1.2-5.1; p=0.016), CS 2.8 (95% CI:1.7- 4.7; p < 0.0001), CNO 3.1 (95% CI:1.7-5.8; p < 0.0001) in IVF pregnancies. These remained statistically significant after adjusting for maternal age. The risk of GDM, IUGR and IUFD was not significantly different between the two groups. Out of 102 IVF conceptions, 47 used donor eggs. These outcomes were not significantly different between donor and autologous oocyte pregnancies. CONCLUSION: IVF treatment is associated with adverse maternal and neonatal outcomes whereas oocyte donation does not improve these outcomes in women 40 years and older.